The Effect of Ethephon on the Berry Colour of Flame Seedless and Bonheur Table Grapes - Lombard, P.J.; Viljoen, J.A.; Wolf, E.E.H.; Calitz, F.J. (South African Journal of Enology and Viticulture, 2017)
Flame Seedless grafted onto Richter 99 situated in the Lower Orange River region and Bonheur grafted onto Ramsey in the Berg River Valley region of South Africa were used to test ethephon treatments for berry colour improvement. The trial was repeated over three seasons. Four ethephon dosages (100, 200, 300 and 400 mg/L) in combination with five application times (weekly intervals starting from acid maximum) were compared to an untreated control. As soon as general minimum maturity for export was reached, pack-out percentage was determined and representative bunch samples harvested and packed as for export. After storage for four weeks at -0.5°C and one week at l0°C, bunch quality was evaluated according to standard industry norms. As a preliminary determination anthocyanin and phenol absorbance levels were determined during one season to possibly complement visual evaluation of berry colour. The best overall result with regard to the timing of application for both Flame Seedless and Bonheur was obtained with an ethephon application two weeks after acid maximum (30 to 40% colour). Significant seasonal differences were observed regarding various quality variables of Bonheur. This timing was not very critical for improved export pack-out or meeting the berry colour quality norm. Treatments closer to harvest increase the risk of quality defects during cold storage, such as berry crack, S02 burn, as well as soft and loose berries. An ethephon dosage of 300 mg/L for Flame Seedless and 200 mg/L for Bonheur gave satisfactory results regarding export pack-out, export-quality berry colour at harvest and post-cold-storage quality. The preliminary evaluation of anthocyanin and total phenol absorbance levels did not correlate well with visual evaluation of berry colour, showing the difficulty of sensory determinations for quality evaluation.